EMPOWERMENT OF LOCAL BRAND AWARENESS THROUGH PACKAGING UNIQUENESS AND ITS IMPACT ON PURCHASING INTEREST - Bob Foster; Wawan Hermawan; Rima Rahmayanti (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2019)
Indonesian local brand is lack of brand awareness among Indonesian consumers. One of the local brands that lack of brand awareness is white tea brand. White tea makers in Indonesia meets the issue of absence of innovation in packaging, shopper awareness and frailness in quality. This research aims to test whether product empowerment and brand awareness will influence the interest in buying white tea products with unique packaging as intervening using partial least square as method in data analysis. Data collection uses questionnaire involving 50 consumer samples of white tea brand in Bandung, West Java. This research shows that the uniqueness of packaging has proven to be intervention between brand awareness and empowerment in product, affects or influences the consumer purchasing interest of white tea brand in Bandung, West Java, Indonesia.